Effect of Pre-treatment and Calcination Process on Micro-Structural and Physico-Chemical Properties of Hydroxyapatite derived from Chicken Bone Bio-waste. (2019) - Barua, Emon; Deoghare, Ashish B.; Deb, Payel; Das Lala, Sumit; Chatterjee, Sushovan
Abstract: This study reports the feasibility of isolation of hydroxyapatite (HA) from chicken bone bio-waste and the effect of pre-treatment and calcination process of bones on micro-structural and physico-chemical properties of HA. Chicken bones are treated with acid, alkali and acid-alkali solution followed by calcination at 700, 800 and 900°C respectively. The calcined bones are characterized and compared. It is found that acid treated bones calcined at 900°C yields pure phase of crystalline HA particles of size 600 nm with good pore morphology having pore diameter 208 nm, Ca/P atomic ratio of 1.653 and high thermal stability, ideal for biomedical applications.